2021
DOI: 10.3389/fvets.2021.749547
|View full text |Cite
|
Sign up to set email alerts
|

Disease Risk and Conservation Implications of Orangutan Translocations

Abstract: Critically Endangered orangutans are translocated in several situations: reintroduced into historic range where no wild populations exist, released to reinforce existing wild populations, and wild-to-wild translocated to remove individuals from potentially risky situations. Translocated orangutans exposed to human diseases, including Coronavirus Disease 2019 (COVID-19), pose risks to wild and previously released conspecifics. Wildlife disease risk experts recommended halting great ape translocations during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
10
0
1
Order By: Relevance
“…However, a recent metagenomic study identified divergent caliciviruses in the western honey bee Apis mellifera (PNG bee virus 1, 12 and 9) [ 53 ], suggesting they might also be able to infect invertebrates. We detected four novel species of calicivirus that fall into a clade with PNG bee virus 1 and 12, and “calicivirus mystacina”, a calicivirus found in the lesser short-tailed bat/pekapeka Mystacina tuberculata in New Zealand [ 54 ] ( Figure 8 ). The presence of the bee viruses in this clade raises the possibility that these are all invertebrate viruses, and both our avian viruses and the bat virus may be of dietary origin, although this will need to be resolved with additional sampling.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent metagenomic study identified divergent caliciviruses in the western honey bee Apis mellifera (PNG bee virus 1, 12 and 9) [ 53 ], suggesting they might also be able to infect invertebrates. We detected four novel species of calicivirus that fall into a clade with PNG bee virus 1 and 12, and “calicivirus mystacina”, a calicivirus found in the lesser short-tailed bat/pekapeka Mystacina tuberculata in New Zealand [ 54 ] ( Figure 8 ). The presence of the bee viruses in this clade raises the possibility that these are all invertebrate viruses, and both our avian viruses and the bat virus may be of dietary origin, although this will need to be resolved with additional sampling.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent metagenomic study identified divergent caliciviruses in the western honey bee Apis mellifera (PNG bee virus 1, 12 and 9) [51], suggesting they might also be able to infect invertebrates. We detected four novel species of calicivirus that fall into a clade with PNG bee virus 1 and 12, and “Calicivirus mystacina ”, a calicivirus found in the lesser short-tailed bat Mystacina tuberculata in New Zealand [52] (Figure 8). The presence of the bee viruses in this clade raises the possibility that these are all invertebrate viruses, and both our avian viruses and the bat virus may be of dietary origin, although this will need to be resolved with additional sampling.…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been very few studies carried out on wild orangutans, there is evidence showing that these great apes can contract respiratory diseases of human origin, both viral and bacterial [ 91 ].…”
Section: Example 1: Human Metapneumovirus and Respiratory Syncytial V...mentioning
confidence: 99%